2013
DOI: 10.1088/2043-6262/4/4/045012
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and application of graphene–silver nanowires composite for ammonia gas sensing

Abstract: Graphene, consisting of a single carbon layer in a two-dimensional (2D) lattice, has been a promising material for application to nanoelectrical devices in recent years. In this study we report the development of a useful ammonia (NH3) gas sensor based on graphene–silver nanowires ‘composite’ with planar electrode structure. The basic strategy involves three steps: (i) preparation of graphene oxide (GO) by modified Hummers method; (ii) synthesis of silver nanowires by polyol method; and (iii) preparation of gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 6 publications
(13 reference statements)
0
15
0
Order By: Relevance
“…For example, Katkov et al [45] created a fluorine-functionalized graphene sensor and reached 10.2% response to 10000 ppm of ammonia. The response 3-4% for 0.1% (1000 ppm) NH 3 in Ar was obtained on reduced graphene oxide-silver nanowires [48].…”
Section: Influence Of the Operating Temperature On Nfc Filmmentioning
confidence: 99%
“…For example, Katkov et al [45] created a fluorine-functionalized graphene sensor and reached 10.2% response to 10000 ppm of ammonia. The response 3-4% for 0.1% (1000 ppm) NH 3 in Ar was obtained on reduced graphene oxide-silver nanowires [48].…”
Section: Influence Of the Operating Temperature On Nfc Filmmentioning
confidence: 99%
“…The adsorption process is controlled by insertion of water vapor, while the desorption process was done by extraction of the vapor followed by insertion of dry gaseous Ar. The measurement system that was described in [21] consists of an Ar gas tank, gas/vapor hoses and solenoids system, two flow meters, a bubbler with vapor solution, and an airtight test chamber connected with collect-store data DAQ component. The Ar gas played a role as carrier gas, dilution gas, and purge gas.…”
Section: Characterization Techniquesmentioning
confidence: 99%
“…Lee et al 44 studied the sensing properties of gold nanoparticle decorated CNT as flexible and transparent ammonia gas sensor and found a high recovery time. Nguyen et al 45 studied ammonia sensing by CNT decorated with cobalt nanoparticle at room temperature and found response time 30-50 s with recovery time of 200 s. Tran et al 46 also studied graphene-silver nanowire composite for ammonia sensing and found high response time of 200 s and recovery time 60 s with the purging of the inert gas argon instead of air. Johnson et al 47 reported ammonia sensing of the CNT, graphitic nanoribbon film and found recovery time of 90, 115 s, respectively.…”
Section: Articlementioning
confidence: 99%